Anisotropic Light Transport in White Beetle Scales. Issue 10 (24th June 2015) - Cortese, Lorenzo; Pattelli, Lorenzo; Utel, Francesco; Vignolini, Silvia; Burresi, Matteo; Wiersma, Diederik S.
<x xml:space="preserve">Abstract</x> The extremely brilliant whiteness shown by the Cyphochilus beetle is generated by multiple scattering of light inside the ultrathin scales that cover its body, whose interior is characterized by an anisotropic nanostructured network of chitin filaments. It is demonstrated that the structural anisotropy of the network is crucial in order to achieve high broadband reflectance from such a thin, low‐refractive‐index system.